Group Boundaries, Immigrant Inclusion, and the Politics of Immigrant–Native Relations. (February 2016) - Okamoto, Dina; Ebert, Kim
In multiethnic nation-states experiencing new flows of immigrants, political officials and citizens alike have expressed hostility in the form of demonstrations, campaigns, vandalism, and even policies. Yet local communities have also displayed public support for immigrants in the form of protests and advocacy efforts. Past literature has almost exclusively focused on anti-immigrant activity, using theories of group threat and competition, which suggest that new influxes or large concentrations of immigrants should prompt dominant groups to protect their interests, leading to anti-immigrant attitudes and behaviors. We extend the literature by focusing on pro-immigrant behavior, which we define as efforts initiated by established local residents and organizations to include immigrants in the larger community and/or to improve the lives of immigrants. In contrast to theories of group threat, we put forth the group inclusion model, and contend that demographic and political "threats" operate to break down rather than bolster group boundaries. We also find that when the increasing demographic and political presence of immigrants is coupled with the visibility of immigration, immigrant inclusion thrives. Using a data set of pro-immigrant collective action across 52 U.S. metropolitan areas, we generally find support for our model, and discuss the broader implications for immigrant–native relations.